Multidisciplinary approach in the teaching of dental sculpture and anatomy - Buchaim, Rogério Leone; Andreo, Jesus Carlos; Rodrigues, Antonio de Castro; Gonçalves, Jéssica Barbosa de Oliveira; Daré, Letícia Rossi; Rosa Junior, Geraldo Marco; Buchaim, Daniela Vieira; Oliveira, José Américo de [UNESP] (Soc Chilena Anatomia, 2014)
The purpose of the Dental Sculpture and Anatomy discipline is to introduce undergraduate students to the study of the anatomic and morphological characteristics of permanent and primary human dentition, through classes, books and cognitive and psychomotor activities. This discipline supports the teaching of specific knowledge necessary for a more extensive education, involving interdisciplinarity as a means of knowledge exchange among several areas of dentistry, to achieve comprehensive professional education. Students must recognize the dental morphology from samples of preserved teeth, and reproduce the morphology through three-dimensional models made of stone or wax blocks. In this article, the authors describe the process for producing teeth collars and macro dental models made of stone, their importance and benefits of utilization. The purpose of the study was to encourage the teaching of Dental Sculpture and Anatomy toundergraduate students of the Bauru School of Dentistry, University of Sao Paulo, through activities that would associate theory, practice and the development of manual skills.

El propósito de la disciplina sobre escultura y anatomía de dientes es introducir a los estudiantes de pregrado para el estudio de las características anatómicas y morfológicas de la dentición humana permanente y primaria, a través de clases, libros y actividades cognitivas y psicomotoras. Esta disciplina se fundamenta en la enseñanza de conocimientos específicos necesarios para una educación más amplia, que implica la interdisciplinariedad como medio de intercambio de conocimientos entre diferentes áreas en odontología, y de esa forma, lograr una enseñanza profesional integral. Los estudiantes deben identificar la morfología dental a partir de dientes conservados, además de reproducir la morfología a través de modelos tridimensionales elaborados con bloques de yeso tipo piedra o cera. En este estudio, los autores describen el proceso para la producción de collares de dientes y macro modelos dentales hechos de yeso tipo piedra, su importancia y los beneficios de su utilización. El propósito del estudio fue incentivar la enseñanza de la escultura y anatomía dental a los estudiantes de pregrado de la Facultad de Odontología de Bauru, Universidad de São Paulo, a través de actividades que asocian la teoría, práctica y desarrollo de habilidades manuales.
Enfoque multidisciplinario para la enseñanza de escultura y anatomía dental
Keywords: Dental anatomy; Education methods; Undergraduate students; Basic sciences; Anatomía dental; Métodos de enseñanza; Estudiantes de pregrado; Ciencias básicas